Where we work determines what we eat: A qualitative exploration of the multi-dimensional influences on meat consumption when home and office working during the Covid 19 lockdown in London, UK. (1st November 2022) - Pluck, Sophie; Morrison-Saunders, Angus
Abstract: Food choices, including the decision to consume meat, are complex and determined by many inter-related influences. This study examined the choice of working professionals to consume meat in the context of forced changes in working conditions during lockdowns in London during the Covid 19 outbreak in 2020–21. Guided by an adapted Ecological Framework depicting influences on food choice in this context, semi-structured interviews were conducted with 33 employees of a financial services consultancy who normally work from offices in central London but were homeworking at the time of research. Food choices associated with all meals (but especially lunches) when working in each setting were explored. Four key themes emerged from the research. Firstly, when office-working the influence of colleagues (social environment factor) on the choice to consume meat was variable and individual-level factors, particularly personality traits, impacted the extent of social influence. Secondly, limited availability of non-meat options and preferences for buying meat-based meals outside the home (physical environment factor), contributed to more meat consumption when office-working. Thirdly, alignment of food choices between household members (social environment factor), largely for convenience reasons, resulted in a greater likelihood of non-meat meals being eaten when homeworking. Finally, not having to commute (physical environment factor) meant participants had more time available, resulting in changes to routines and priorities (individual-level factors), with some reduced meat consumption. Overall, research findings contribute to building understanding of how both home and office-working influence the choice to consume meat. Findings may be used to inform strategies to reduce meat consumption, which will in turn play a role in supporting global climate change targets and reducing harm to the natural environment associated with food choices.